STUDI FENOMENOLOGI PADA PERILAKU SEKSUAL MAHASISWA DI KOTA MAKASSAR - Dwia Aries Tina Pulubuhu; Mansyur Radjab; Nufida RAF; Arsyad Genda; Suryanto Arifin; Meigi Marulina Patading (Department of Sociology Faculty of Social and Political Sciences, 2020)
The purpose of the study was to reveal the phenomenon of students' sexual experiences, to analyze the process of relationships in sexual behavior and to identify and analyze the forms of sexual activity / behavior of students in the city of Makassar. This study uses a qualitative approach, with a phenomenological strategy / design. The subjects of this study were 5 (five) informants who were students or had just finished their education and were still in sexual activity / behavior. The results of this study show 3 findings namely; (1). All informants considered that they did not violate social norms. Because their sexual activity always refers to the standard